1985
DOI: 10.1104/pp.78.1.34
|View full text |Cite
|
Sign up to set email alerts
|

A Supernodulation and Nitrate-Tolerant Symbiotic (nts) Soybean Mutant

Abstract: The nodulation characteristics of soybean (Glycine max) mutant nts382 are described. The mutant nodulated significantly more than the parent cultivar Bragg in the presence and absence of several combined nitrogen sources (KNO3, urea, NHsCI, and NH4NO3). The number of nodules on the tap root and on lateral roots was increased in the mutant line. In the presence of KNO3 and urea, nitrogenase activity was considerably higher in nts382 than in Bragg. Mutant medium (20). To a lesser extent, other sources of comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
187
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(192 citation statements)
references
References 15 publications
5
187
0
Order By: Relevance
“…The number of nodules is regulated in at least two ways: by aborting infection and by confining the nodulation zone. Defects in these mechanisms, caused by genetic mutation lead to hyper-or super-nodulation (Carroll et al 1985;Caetano-Anollès and Gresshoff 1991;Penmetsa and Cook 1997;Nishimura et al 2002;Krusell et al 2002;Oka-Kira et al 2005). On the other hand, a strict interdependence exists between the level of nitrogenase activity and the efficiency of carbon sources flux providing energy for the bacteroid-mediated N 2 reduction (Pathirana et al 1992;Schulze et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The number of nodules is regulated in at least two ways: by aborting infection and by confining the nodulation zone. Defects in these mechanisms, caused by genetic mutation lead to hyper-or super-nodulation (Carroll et al 1985;Caetano-Anollès and Gresshoff 1991;Penmetsa and Cook 1997;Nishimura et al 2002;Krusell et al 2002;Oka-Kira et al 2005). On the other hand, a strict interdependence exists between the level of nitrogenase activity and the efficiency of carbon sources flux providing energy for the bacteroid-mediated N 2 reduction (Pathirana et al 1992;Schulze et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most successful "breeding for fixation" outcomes is the soybean program in Brazil (Alves et al, 2003), which as a result of continual evaluation of inoculated plants growing in now nitrogenous soils, has resulted in the development of lines that realize their full symbiotic potential. Mutant lines of soybean, pea, common bean and Lotus japonicus have also been generated that nodulate super abundantly (hyper-nodulation; Carroll et al, 1985). As single recessive gene controls the hyper-nodulation trait in soybean but despite potential utility, this gene has not been yet incorporated into commercial cultivars.…”
Section: Case Studies On Cotton (Gossypium Hirsutum) and Some Legumesmentioning
confidence: 99%
“…Split-root experiments demonstrated that infection of the root by rhizobia induces a signal that moves to the shoot and activates NARK, and subsequently, a signal is sent back from the shoot to the root to inhibit further nodule development, at least temporarily (Kosslak and Bohlool, 1984). Interestingly, autoregulation mutants also show the nts phenotype (Carroll et al, 1985b;Sagan et al, 1995); that is, they still nodulate in the presence of nitrate concentrations that inhibit nodulation in the wild type, although various mutants differ in their degree of nitrate tolerance. Again, grafting studies showed that the nts phenotype is exerted by the shoot in soybean and M. truncatula (Day et al, 1989;Sagan et al, 1995;Jeudy et al, 2010).…”
mentioning
confidence: 99%
“…Mutation of these autoregulation genes causes supernodulation, mostly even in the presence of high N concentrations, and were thus first termed nitrate tolerant symbiotic (nts) mutants in soybean (Glycine max; Carroll et al, 1985aCarroll et al, , 1985b.…”
mentioning
confidence: 99%